ZONASI FORAMINIFERA PLANKTONIK DAERAH GUNUNG KINJENG DAN GUNUNG GEDE KECAMATAN SENTOLO KABUPATEN KULON PROGO DAERAH ISTIMEWA YOGYAKARTA - Sanjoto, Siwi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2010)
Stratigraphic analizes for samples from the Sentolo Formation is marl and carbo-naceous sandstone on Gunung Gede and Gunung Kinjeng, were examined for foramini-feral occurence. About fourty eight species of microplanktonic and twenty seven species of microbenthonic were identified. They have been studied previously in this three family Globigerinidae, Globorotalidae, Hantkenidae. This family clasificasied from one super fa-mily Globigerinacea. The analizes species of microplanktonic fosils have been correlated with N-9 Gunung Gede samples, and Gunung Kinjeng samples N12-N14 (Middle Mio-sen). The microbenthonic fosils have been identified that which depositional environment of the Sentolo Formation was Upper Bathyal.